MitoNeoD: A Mitochondria-Targeted Superoxide Probe. Issue 10 (19th October 2017) - Shchepinova, Maria M.; Cairns, Andrew G.; Prime, Tracy A.; Logan, Angela; James, Andrew M.; Hall, Andrew R.; Vidoni, Sara; Arndt, Sabine; Caldwell, Stuart T.; Prag, Hiran A.; Pell, Victoria R.; Krieg, Thomas; et al.
Summary: Mitochondrial superoxide (O2 ⋅− ) underlies much oxidative damage and redox signaling. Fluorescent probes can detect O2 ⋅−, but are of limited applicability in vivo, while in cells their usefulness is constrained by side reactions and DNA intercalation. To overcome these limitations, we developed a dual-purpose mitochondrial O2 ⋅− probe, MitoNeoD, which can assess O2 ⋅− changes in vivo by mass spectrometry and in vitro by fluorescence. MitoNeoD comprises a O2 ⋅− -sensitive reduced phenanthridinium moiety modified to prevent DNA intercalation, as well as a carbon-deuterium bond to enhance its selectivity for O2 ⋅− over non-specific oxidation, and a triphenylphosphonium lipophilic cation moiety leading to the rapid accumulation within mitochondria. We demonstrated that MitoNeoD was a versatile and robust probe to assess changes in mitochondrial O2 ⋅− from isolated mitochondria to animal models, thus offering a way to examine the many roles of mitochondrial O2 ⋅− production in health and disease. Graphical Abstract: Highlights: MitoNeoD is a mitochondria-targeted O2 ⋅− probe that can be used in vivo Neopentyl groups prevent DNA intercalation by MitoNeoD and its derivatives Incorporation of a carbon-deuterium bond enhances O2 ⋅− selectivity by MitoNeoD MitoNeoD extends methods available to assess mitochondrial O2 ⋅− Abstract : Current methods to assess mitochondrial O2 ⋅− cannot be applied in vivo and are artifact prone. Here Shchepinova et al. introduce MitoNeoD, which can be used to assess changes in mitochondrial O2 ⋅− by fluorescence and by mass spectrometry.